Essays on Asset Pricing with Financial Frictions - Sven Klingler (Copenhagen Business School (CBS), 2017)
The rst essay focuses on Credit default swap (CDS) premiums of safe sovereigns, that is, the insurance against the default of countries with a low credit risk, like Germany, Japan, or the United States. We motivate the essay by establishing the following two stylized facts. First, we document that there is a large market for insurance against the default of safe sovereigns and that the CDS premiums for these sovereigns are substantial, sometimes exceeding 100 basis points. Second, we show that there is virtually no relationship between CDS premiums and bond yield spreads, which are measured as the spread between bond yield and risk-free rate, for safe sovereigns. This nding is in opposition to the no-arbitrage theory that CDS premiums and yield spreads should move in lockstep. Motivated by these stylized facts, we investigate the following two questions: First, what are the motives behind purchasing insurance against the default of safe sovereigns? Second, what drives safe-haven CDS premiums if not credit risk?
hdl:10398/9502
Keywords: 650